FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PEMANFAATAN E-MARKETING TANI NIAGA OLEH PETANI KABUPATEN GROBOGAN - Ariska Rosadi Al Rasyid Shodiq; Wahyu Budi Priatna; Nunung Kusnadi (Forum Agribisnis, 2019)
Most e-marketing is widely used for business activities by companies in marketing non-agribusiness products. This happens because agribusiness products have different characteristics from non-agribusiness products, that is perishable, voluminous, and bulky. Although in its development, agribusiness products can also be marketed through e-marketing. Tani Niaga is one of the e-marketing in the agribusiness sector, which managed by the Agriculture Service of Grobogan Regency (Dinas Pertanian Kabupaten Grobogan). The purpose of research are to identify factors that influence farmer to use Tani Niaga. The data were analyzed using Partial Least Square (PLS) to identify factors that influenced farmer to use Tani Niaga. The results of research showed that the individual characteristics of farmers and the characteristics of the Tani Niaga had significant effect on using Tani Niaga. The formal education was a dominant factor in individual characteristics of food farmers whose a significant effect on the level of using of the Tani Niaga, but a dominant factor in the horticulture farmers group was the courage to take risks. Moreover, the suitability of need was a dominant factor for the characteristic of Tani Niaga whose a significant effect on the level of using the Tani Niaga in the group of food farmers, but ease-of-use the Tani Niaga was a dominant factor for the group of horticultural farmers.